Use of mifepristone for termination of intrauterine fetal demise (IUFD) in previously scarred uterus in later half of pregnancy (>20 weeks) - Arora, R.; Patel, P. B.; Dabral, A.; Sachdeva, M.; Arya, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Mifepristone has the potential to be used as an agent for induction of labour by increasing the uterine contractility and increasing the sensitivity of uterus to prostaglandins. The present study is an endeavor to study the effect of mifepristone alone to induce labour in scarred uterus and its risk benefit ratio. Methods: Total 39 patients with IUFD and previous uterine surgery were included in the study after their informed consent. All women in the study were given Tablet Mifepristone 200 mg orally, thrice a day, maximum 6 doses (Max -1200 mg) over a duration of 48 hours. Patients were monitored for vitals, the uterine contractions and any bleeding per vaginum. Next dose of drug was omitted if sufficient uterine contractions or cervical dilatation ≥2.5 cm achieved. Patients were shifted to the labour room after onset of active labour. Labour was augmented with oxytocin wherever required. Results: spontaneous labour occurred in 74.3% (29/39) women while operative (cesarean/ hysterotomy) delivery occurred in 17.9% (07/39). Mean induction (first dose of mifepristone) to delivery interval was 51.5 hrs in second trimester while 59.8 hrs in third trimester women. Oxytocin augmentation was done in 8 (20.5 %) women. Conclusions: The potential advantage of mifepristone over prostaglandins and oxytocin, is mainly in situations where they are contraindicated (i.e., scarred uterus). In this study authors found that with mifepristone only regimen is quite safe and effective, inducing spontaneous labour in 74.3% (29/39) women with IUFD and in reducing the operative (cesarean/ hysterotomy) delivery (17.9%).